Pre-processing of gender-based comparative usability performance data in Mobile Augmented Reality English language teaching - Lim K.C.; Selamat A.; Ghani N.A.M.; Zabil M.H.M.; Alias R.A.; Puteh F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer aided instruction; E-learning; Students; Teaching; Usability engineering; Application builds; English language teaching; English languages; Gender-based; Mobile augmented reality; Pre-processing stages; Project prioritization; Usability; Augmented reality